Write the expression


Write the expression nCr +1 + nCr − 1 + 2 × nCr in the simplest form.


${ }^{n} C_{r+1}+{ }^{n} C_{r-1}+2 \cdot{ }^{n} C_{r}$

$=\left({ }^{n} C_{r+1}+{ }^{n} C_{r}\right)+\left({ }^{n} C_{r}+{ }^{n} C_{r-1}\right) \quad\left[{ }^{n} C_{r}+{ }^{n} C_{r-1}={ }^{n+1} C_{r}\right]$

$={ }^{n+1} C_{r+1}+{ }^{n+1} C_{r} \quad\left[{ }^{n} C_{r}+{ }^{n} C_{r-1}={ }^{n+1} C_{r}\right]$

$={ }^{n+2} C_{r+1}$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now